Pelatihan Pembuatan Pupuk Organik Cair dari Limbah Sayuran dan Kulit Buah - Faizah, Iva; Sagita, Novalia; Amrina, Dania Hellin (Universitas Islam Negeri Raden Intan Lampung, 2021)
This community service project in the form of training was carried out on the basis of the collaboration of KKN-DR students from UIN Raden Intan Lampung and the Tanjung Jati village community, with the help of Tanjung Jati village officials in the southern coastal district of the west coast district of Lampung Province, in order to provide product training for the community and Pekon Tanjung Jati officials make liquid organic fertilizer from vegetable waste to fertilize plants. The method used is by socializing, practicing and providing training to the community and village officials which is held at the village hall of Tanjung Jati. The purpose of this service is as a means of education and processing vegetable waste to fertilize plants. As a result, people are very aware that vegetable waste that is recycled into liquid organic fertilizer has benefits for fertilizing plants.